ANALISIS SEKTOR BASIS DAN PERGESERAN STRUKTUR PEREKONOMIAN KABUPATEN SEKADAU - HARSONO, BAYU DWI (Jurnal Ekonomi Daerah (JEDA), 2013)
ABSTRACT The title of this research is the analysis of the basis sector and the shift in economic structure Sekadau District. District Sekadau born with the issuance of the Constitution Act number 34 in 2003 about the formation of the Sekadau District and Melawi District in West Kalimantan. Successful development Sekadau district can be seen from the growth of the economy itself that can be known through Gross Domestic Product growth in time series from year to year. Through GDP seen what sectors are the basis of the economy in Sekadau District . District Government to take appropriate steps in the process of further development. The analysis tools are Locations quotients (LQ) analysis. The shift in economic structure Sekadau District to determine the extent of the growth of regions, economic sectors which are growing faster than similar sectors in the higher areas and which sectors have a higher competitiveness than similar sectors in West Kalimantan . analysis tools is Shift-share analysis Then to know which sectors are a priority to be developed and where the potential for more developed, which sectors are advanced but depressed and left.The analysis tools are Quotients Klassen analysis. Based on the results of the analysis of the base economic sectors in the District Sekadau is agriculture and mining and quarrying.While the sectors are growing faster than similar sectors in the province of West Kalimantan were mining and quarrying; building sector; transport and communications; finance, leasing and service companies as well as sector services. Sectors that have a higher competitiveness than similar sectors in West Kalimantan is the agricultural sector; electricity, gas and water supply; construction sector, as well as trade, hotels and restaurants.While the economic sector is a priority to develop the agricultural sector; electricity, gas and water supply; sectors of construction and trade, hotels and restaurants. Keywords: Base sector, shifting the economic structure as well as the priority economic sectors